Medical and pharmacy students' attitudes towards physician-pharmacist collaboration in Kuwait - Katoue MG; Awad AI; Al-Jarallah A; Al-Ozairi E; Schwinghammer TL (Centro de Investigaciones y Publicaciones Farmaceuticas, 2017)
Objective: To assess and compare the attitudes of medical and pharmacy students towards physician-pharmacist collaboration and explore their opinions about the barriers to collaborative practice in Kuwait. Methods: A cross-sectional survey of pharmacy and medical students (n=467) was conducted in Faculties of Medicine and Pharmacy, Kuwait University. Data were collected via self-administered questionnaire from first-year pharmacy and medical students and students in the last two professional years of the pharmacy and medical programs. Descriptive and comparative analyses were performed using SPSS, version 22. Statistical significance was accepted at p<0.05. Results: The response rate was 82.4%. Respondents had overall positive attitudes towards physician-pharmacist collaboration. Pharmacy students expressed significantly more positive attitudes than medical students (p< 0.001). Medical students rated the three most significant barriers to collaboration to be: pharmacists' separation from patient care areas (n=100, 70.0%), lack of pharmacists' access to patients' medical record (n=90, 63.0%) and physicians assuming total responsibility for clinical decision-making (n=87, 60.8%). Pharmacy students' top three perceived barriers were: lack of pharmacists' access to patients' medical record (n=80, 84.2%), organizational obstacles (n=79, 83.2%), and pharmacists' separation from patient care areas (n=77, 81.1%). Lack of interprofessional education was rated the fourth-largest barrier by both medical (n=79, 55.2%) and pharmacy (n=76, 80.0%) students. Conclusions: Medical and pharmacy students in Kuwait advocate physician-pharmacist collaborative practice, but both groups identified substantial barriers to implementation. Efforts are needed to enhance undergraduate/postgraduate training in interprofessional collaboration, and to overcome barriers to physician-pharmacist collaboration to advance a team approach to patient care.